SELF-MANAGEMENT GOAL SETTING AMONG WOMEN DIAGNOSED WITH GESTATIONAL DIABETES MELLITUS; A CROSS-SECTIONAL STUDY IN A LOW-INCOME SETTING IN CENTRAL UGANDA. - Serunjogi, David; Ejalu, David Livingstone (Student's Journal of Health Research Africa, 2024)
Background: Copying with a diagnosis of Gestational Diabetes Mellitus (GDM) is very stressful and the task of GDM Self-management is challenging given the circumstances that surround the diagnosis amidst the challenges of pregnancy. In Uganda, little is known about how women diagnosed with the condition manage it through pregnancy. The study assessed the prevalence of self-management goal setting and associated factors among women diagnosed with Gestational Diabetes Mellitus in a low-income setting in central Uganda. Methodology: A cross-sectional study was done among 245 women who attended antenatal care in the selected 16 health facilities within Wakiso district, central Uganda who were diagnosed with GDM during their visit to the Clinics from July 2021 to May 2022. Data was collected using telephone interviews, and analyzed using SPSS, the results were reported in the form of tables and figures. Data was collected from March 2023 to May 2023. Results: The majority 123(53.9%) of the respondents were aged between 28 to 37 years old. Only 17% (n=41) of women diagnosed with GDM managed to set a self-management goal. The common self-management goals set include doing 1-2 Ultrasound scans during pregnancy to monitor the baby 82.93%(n=34%), followed by doing regular exercises 63.41% (n=26) and eating a regular diet every day 53.66% (n=22). Conclusion: Only a small proportion of women diagnosed with GDM can set self-management goals with common goals being doing Ultrasound scans, regular exercise, and eating regular diets. Recommendation: There is a need for public health specialists to study the factors that might be associated with setting self-management goals in a low-income setting of Wakiso district, Uganda.